Influence Dynamics of Ratu Dwi Anjani as a Sacred Female Figure on Mount Rinjani Lombok: An Ecofeminist Study of the Nahdatul Wathan Organisation - Fadhilatillaili Arianingsih (ASTEEC, 2024)
This article explores ethnographically the relationship between the feminine and indigenous sasak ideas through the figure of the sacred female jinn spirit queen Dewi Anjani who rules Lombok. As a sacred woman who rules Lombok from Mount Rinjani, Ratu Dwi Anjani is embedded in the beliefs and traditions of the Sasak people that shape the praxis of feminine spirituality of women in the Nahdatul Wathan organisation. Ratu Dwi Anjani is a representation of the agency of indigenous Sasak Lombok women who form mystical and sacred experiences and provide a comprehensive meaning of life between gender and the maintenance of goddesses or female ancestors who are respected and have power in invisible myths. The approach used is a qualitative data analysis approach withlibrary research. This research aims to deepen understanding of the complexities embedded in the interaction of sacred women, gender, nature and Islam in Lombok. The results of this research present a new argument that shows how the indigenous Ratu Jin as a feminine form of God influences the discourse of Muslim holy women to carry out an integral role in the orthopraxy of the Nahdatul Wathan organization.